(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To evaluate the clinical characteristics of medium to large Т1-Т4 choroidal melanomas (CM) in patients treated at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine”. Material and Methods. We retrospectively reviewed the medical records of 283 patients treated for medium to large CM at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” in 2007-2024. The study sample consisted of 125 men (44.2%) and 158 women (55.8%), with a mean age (standard deviation (SD)) of 54.2 (12.4) years. Patients underwent standard ophthalmological examination. Additionally, they received ocular ultrasonography using a Cinescan ultrasound system, OCT examination using a Stratus OCT 300 system and fluorescein angiography. No metastasis was detected in any patient at presentation and the start of treatment. Results. The case distribution included stage T1 in 15 patients (5.3%), stage T2 in 132 patients (46.64%), stage T3 in 115 patients (40.64%), and stage T4 in 21 patients (7.42%). Paramacular and peripheral locations of CM were more common in the total sample (88.4%) (p <0.05), and stages T2 (59 [44.7%] and 53 [40.15%], respectively) and T3 (60 [52.17%] and 50 [43.48%], respectively), and were the only two locations seen in stage T4 (10 [47.62%] and 11 [52.38%], respectively). Parafoveal and juxtapapillary tumor locations were seen in stages T1 to T3 (10 [3.53%] and 23 [8.13%], respectively, of the 283 patients), and were more common in stage T2 (6 [60.0%] and 14 [60.87%], respectively). Heterogeneously pigmented CM were most common (132 [46.64%]), followed by mildly pigmented (104 [36.75%]), pigmented (41 [14.49%]) and amelanotic (6 [2.12%]). There were no amelanotic cases in stages T1 and T4. Mildly pigmented CM were present among tumors of any stage, and were most common in stage T2 (60 [21.2%]). Heterogeneously pigmented and pigmented CM were present among tumors of any stage, and were more common in stages T3 (62 [53.91%]) and T2 (54 [40.91%]). T4 tumors were predominantly heterogeneously pigmented and pigmented (13 [61.9%] and 5 [23.81%], respectively) (p < 0.05). Among 283 cases of CM, 147 (147 (51.9%) were dome-shaped, 73 (25.8%) were mushroom-shaped, 54 (19.1%) were finger-shaped and 9 (3.2%) were multilobulated. All patients had diffuse tumors without distinct borders, with a secondary retinal detachment above and around the tumor. Conclusion. We examined the clinical signs depending on the stage of CM. These signs have a prognostic value for the efficacy of treatment, which will be reported subsequently.